Differential impact of obesity on the pathogenesis of RA or preclinical models is contingent on the disease status. Issue 4 (18th October 2016) - Kim, Seung-jae; Chen, Zhenlong; Essani, Abdul B; Elshabrawy, Hatem A; Volin, Michael V; Fantuzzi, Giamila; McInnes, Iain B; Baker, Joshua F; Finn, Patricia; Kondos, George; Volkov, Suncica; Swedler, William; et al.
Abstract : Objective: Studies were performed to uncover the significance of obesity in rheumatoid arthritis (RA) and preclinical models. Methods: Preclinical arthritis models were used to examine the impact of obesity on disease onset and remission. Conditioned media from RA adipose tissues were used to investigate the mechanism contributing to joint neutrophil influx and M1 macrophage differentiation observed in early and remission phases of arthritis. Results: We report that mice fed with high fat diet (HFD) have an earlier onset of collagen-induced arthritis (CIA) compared with mice on regular diet. However, the differences in CIA joint swelling between the two diet groups are lost once disease is established. We found that early arthritis triggered by obesity is due to elevated joint MIP2/interleukin-8 levels detected in CIA as well as in the RA and mouse adipose tissues and the effect of this chemokine on neutrophil recruitment. Although active disease progression is similarly affected in both diet groups, arthritis resolution is accelerated in lean mice while joint inflammation is sustained in obese mice. We document that HFD can prolong toll-like receptor (TLR)4-induced arthritis by increasing joint monocyte migration and further remodelling the recruited cells into M1 macrophages. Consistently, we show that adipose condition media can transform RA and wild-type naïve myeloid cells into M1 macrophages; however, this function is impaired by TLR4 blockade or deficiency. Conclusions: We conclude that despite established disease being unaffected by obesity, the early and the resolution phases of RA are impacted by obesity through different mechanisms.